Nodular Regenerative Hyperplasia - Mindy Lee MD; Manhal Izzy MD; Ashwin Akki MD; Kathryn Tanaka MD; Harmit Kalia DO (SAGE Publishing, 2017)
Introduction: Nodular regenerative hyperplasia (NRH) is a known etiology of noncirrhotic portal hypertension. Cases of biopsy-proven NRH in human immunodeficiency virus (HIV)-positive patients have been described. While these patients often have normal synthetic liver function, several reports described disease progression to liver failure. Case: We here present a 26-year-old woman with history of congenital HIV on antiretroviral therapy complicated by Pneumocystis carinii pneumonia at age 14. CD4 counts have been >300 with undetectable viral load. She was referred to our Hepatology service for evaluation of splenomegaly, elevated liver tests, and thrombocytopenia. On initial presentation, she reported easy bruising and gingival bleeding, and abdominal imaging showed evidence of portal hypertension without associated cirrhosis. Upper endoscopy was significant for large esophageal varices without bleeding stigmata. Liver biopsy showed minimal fibrosis around the portal areas without significant inflammation. The lobules showed focal zones of thin hepatocyte plates on reticulin stain with adjacent areas showing mild regenerative changes. The diagnosis of NRH was made and patient was placed on propranolol for variceal bleeding prophylaxis. Two years later, the patient presented with bleeding gastric varices warranting transjugular intrahepatic portosystemic shunt. Postprocedure course was complicated by mild encephalopathy. Subsequent magnetic resonance imaging showed a 1.7 × 1.3 cm lesion suggestive of hepatocellular carcinoma (HCC). The patient was deemed to be a candidate for liver transplantation, and she is now delisted due to ongoing pregnancy. Conclusion: This report describes the first case of HCC in an HIV patient with NRH. The possible association of NRH with HCC warrants further investigation.